Pengaruh Penggunaan Media Audio Visual terhadap Keterampilan Menulis Karangan Persuasi pada Siswa Kelas X SMA Muhammadiyah 3 Kota Tangerang - Enawar Enawar; Sumiyani Sumiyani (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to determine the effect of using audio-visual media on the skills of writing persuasive essays in class X SMA 3 Tangerang City. The research method used is a quasi-experimental method with a nonequivalent control group design. Data collection techniques using tests. The data analysis technique starts from the normality test, homogeneity test, and hypothesis testing. The results showed that there was an effect of using audio-visual media on the skills of writing persuasive essays in class X SMA 3 Tangerang City. This effect is shown from the comparison of the post-test value of the experimental class of 71.3 and that of the control class of 66.8. Then, from the results of the hypothesis test tcount of 4.59 > ttable of 2.00, then there is a significant difference in the final test results of students in the experimental class and students in the control class. This means that the experimental class students are more skilled at writing persuasive essays after the application of audiovisual media than students in the control class who do not use audiovisual media.